Enterovirus D68 infection in a cluster of children with acute flaccid myelitis, Buenos Aires, Argentina, 2016. (November 2017) - Ruggieri, Victor; Paz, Maria Ivana; Peretti, María Gabriela; Rugilo, Carlos; Bologna, Rosa; Freire, Cecilia; Vergel, Silvana; Savransky, Andrea
Abstract: Objective: To report a outbreak of 11 cases of acute asymmetric flaccid myelopathy due to spinal motor neuron injury. Material and methods: Eleven children, six male, with a mean age of 3 years presented with acute flaccid myelitis. We analyzed clinical features, etiology, neuroradiological images, treatment, and outcome. Results: Nine children had bilateral and asymmetric flaccid myelitis of the upper limbs, 1 had upper limb monoplegia, and 1 presented with hemiparesis. The cranial nerves were involved in 6 patients and 4 required mechanical ventilation. In all cases acute flaccid myelitis co-occurred with upper airway infection and/or fever. Spinal cord magnetic resonance imaging was abnormal in all, showing 2 different patterns: A linear pattern involving the anterior horns and another that was more heterogeneous showing spinal cord expansion. The lesions were non-enhancing in all. In 5/11 patients involvement of the medulla oblongata and pons was also observed. None of the patients presented with supratentorial lesions. In 4/11 children, the human enterovirus subtype D68 (HEV-D68) was identified in the airway and in 1/11 in the cerebrospinal fluid as well. In the remaining patients different enterovirus species A, B, and C variants were detected, as well as rhinovirus in 1 and influenza in another. Ten children received treatment with intravenous immunoglobulin and steroids and 4 of these children also underwent plasma exchange. Treatment did not lead to clinical improvement. Conclusions: In a patient with acute flaccid myelitis, HEV-D68 infection should be ruled out. Cases in which the virus was not detected were considered as "false negatives" as samples were collected late in course of the disease. The lack of response to anti-inflammatory and immunomodulatory treatment suggests a direct viral mechanism. This study is to our knowledge the first on an HEV-D68-infection-related cluster in Latin America. Highlights: Enterovirus-D68- may be associated to acute flaccid myelitis in children. Short-term outcome related to enterovirus-D68 is associated with severe poliomyelitis like neurological deficits. When HEV-D68-associated flaccid myelitis is suspected, nasopharyngeal swab is the method of choice to search the viral agent. To avoid false negative, nasopharyngeal swab should have been taken in the first week.